p110δ PI3 kinase pathway: emerging roles in cancer - Tzenaki, Niki; Papakonstanti, Evangelia A. (Frontiers in Oncology, 2013)
Class IA PI3Ks consists of three isoforms of the p110 catalytic subunit designated p110a, p110b and p110d which are encoded by three separate genes. Gain-of-function mutations on PIK3CA gene encoding for p110a isoform have been detected in a wide variety of human cancers whereas no somatic mutations of genes encoding for p110b or p110d have been reported. Unlike p110a and p110b which are ubiquitously expressed, p110d is highly enriched in leukocytes and thus the p110d PI3K pathway has attracted more attention for its involvement in immune disorders. However, findings have been accumulated showing that the p110d PI3K plays a seminal role in the development and progression of some hematologic malignancies. A wealth of knowledge has come from studies showing the central role of p110d PI3K in B-cell functions and B-cell malignancies. Further data have documented that wild-type p110d becomes oncogenic when overexpressed in cell culture models and that p110d is the predominant isoform expressed in some human solid tumor cells playing a prominent role in these cells. Genetic inactivation of p110d in mice models and highly-selective inhibitors of p110d have demonstrated an important role of this isoform in differentiation, growth, survival, motility and morphology with the inositol phosphatase PTEN to play a critical role in p110d signaling. In this review, we summarize our understanding of the p110d PI3K signaling pathway in hematopoietic cells and malignancies, we highlight the evidence showing the oncogenic potential of p110d in cells of non-hematopoietic origin and we discuss perspectives for potential novel roles of p110d PI3K in cancer.